2013
DOI: 10.1016/j.ijdevneu.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The effects of prenatal exposure to valproic acid on the initial development of serotonergic neurons

Abstract: In utero exposure to valproic acid (VPA) may cause symptoms related to autism spectrum disorder (ASD). An abnormal serotonergic (5-HT) system has been implicated in the etiology of ASD. In the present study, we have examined the expression and distribution of two early inducers of 5-HT neurons in rat embryos, to elucidate the prenatal development of 5-HT neurons after VPA exposure at embryonic day (E) 9.5. Whole-embryo in situ hybridization at E11.5 showed that the expression of sonic hedgehog, one of the earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 45 publications
2
17
0
1
Order By: Relevance
“…They found that the index could distinguish between neurotoxic and non-neurotoxic chemicals. Recently, Jacob et al used the antibody to label serotonergic neurons and revealed that serotonergic differentiation failed in a zebrafish model of fetal valproate syndrome (Jacob et al 2014), which is highly consistent with rodent models of fetal valproate syndrome (Miyazaki et al 2005;Kuwagata et al 2009;Oyabu et al 2013).…”
Section: Neuroimagingmentioning
confidence: 67%
“…They found that the index could distinguish between neurotoxic and non-neurotoxic chemicals. Recently, Jacob et al used the antibody to label serotonergic neurons and revealed that serotonergic differentiation failed in a zebrafish model of fetal valproate syndrome (Jacob et al 2014), which is highly consistent with rodent models of fetal valproate syndrome (Miyazaki et al 2005;Kuwagata et al 2009;Oyabu et al 2013).…”
Section: Neuroimagingmentioning
confidence: 67%
“…[47][48][49][50][51] A growing body of evidence suggests that the state-like and oscillatory interactions of gene products within and extending from the Shh signaling pathway (Figure 3), 49,50,52,53 and modulated by environmental factors, could constitute the basis for the wide range of phenotypic manifestations of BPAD. [54][55][56] Antidepressant drugs, 57 including lithium, 58 and electroconvulsive therapy 59 have been shown to alter Shh signaling. Glycogen synthase kinase 3 (GSK3; GSK3α/GSK3β) is a target of lithium and has a central role in Shh signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the s-allele of the 5-HTTLPR has also been associated with anxiety (Kenna et al, 2012 ) and cognitive deficits (Weiss et al, 2014 ), which are also prominent in patients with ASD, as mentioned above. Since prenatal valproate significantly affects serotonergic neurotransmission (Miyazaki et al, 2005 ; Oyabu et al, 2013 ), the present study investigates the potential interaction between valproate and a genetic reduction of the SERT. More specifically, we injected heterozygous SERT knock-out and wildtype rats prenatally with a moderate dose (400 mg/kg s.c.) of valproate and investigated the behavior of the offspring in two models for anxiety (elevated plus maze and novelty suppressed feeding) and two models assessing cognition and information processing (latent inhibition and prepulse inhibition).…”
Section: Introductionmentioning
confidence: 99%